Liability Payment System at PT. Indonesia Power PLTU Banten 2 Labuan OMU - Wiwin Widiawati (PT. EQUATOR SINAR AKADEMIA, 2021)
The purpose of writing this thesis report is to determine the liability payment system and factors that are obstacles in the payment system of liabilities at PT. Indonesia Power PLTU Banten 2 Labuan OMU. The object of this thesis is the liability at PT. Indonesia Power PLTU Banten 2 Labuan OMU. The writing method used is the interview method and the documentation method. The type of data used is primary data and secondary data. Sources of data obtained from direct research and literature studies. How to collect data through observation, interviews, and documentation. The results of the study that the payment system used at PT. Indonesia Power PLTU Banten 2 Labuan OMU using Cash Management Bank / BNI Direct. The obstacle that occurs at the time of payment of a liability is poor cash management.